Market-based capabilities and financial performance of firms: Insights into marketing's contribution to firm value - RAMASWAMI, Sridhar N. (Institutional Knowledge at Singapore Management University, 2009)
While there is recognition that market-based capabilities contribute to a firm’s financial performance, the exposition is largely conceptual (Srivastava et al. Journal of Marketing 62:2–18, 1998; Journal of Marketing 63:168–179, 1999). Using a resource based view of the firm, the present study proposes that (1) market-based assets and capabilities of a firm impacts (2) performance in three market-facing business processes (new product development, supply-chain and customer management), which in turn, influence (3) the firm’s financial performance. It develops related hypotheses and tests the framework empirically. The study also examines for the first time the interrelationship among the three business processes and their impact on the market value of firms. Further, the study examines the moderating influence of two organizational variables—size and age of the firm. Overall, the major contribution of the study is that it offers a process linkage between capabilities, process performance and financial performance. The results of this research will provide strategic insights to managers on optimal customer management, product development and supply chain strategies.